The Use of Comic Strip in Improving Speaking Skill of EFL Students Through Project-Based Learning at Junior High School - Sudarwinoto, Sudarwinoto; Munir, Munir; Yaman, Suriama (Universitas Negeri Makassar, 2024)
Abstract. This study was pre-experimental research that aimed to find out whether the use of comic strip improves EFL students' speaking skill at UPT SPF SMPN 23 Makassar. The independent variable of this study is the use of comic strip and the dependent variable is the students' speaking skill. The population of this study was all the students of VIII Classes of UPT SPF SMPN 23 Makassar and the sample was VIII.1 class with 37 students. The research sample was selected by using a cluster random sampling. The research data were obtained by giving an assignment about ask and giving information about experiences of Independence Day in dialogue to the pretest and posttest. The analysis technique used in this research was descriptive statistical and inferential statistical techniques. Based on the analysis results, P = 0.000 is smaller than α = 0.05 and the students’ mean score in posttest (76.75) was higher than the students’ mean score in the pretest (57.02). So, it was concluded that the use of comic strip significantly improved the speaking skill of EFL students at UPT SPF SMPN 23 Makassar. This research only focused on the use of Comic Strip in theme Celebrating Independence Day in improving students' speaking skill. Future researchers may be able to conduct research to find out how comic strip can improve other skills such as listening, reading, and writing. Keywords: Comic Strip, Speaking Skill, Project-Based Learning